Footloose multinationals? - Holger Görg; Eric Strobl (Centre for Economic Policy Research (CEPR), 2002)
This Paper examines whether multinational companies are more `footloose' than their domestic counterparts in the host country, using data for the Irish manufacturing sector. First, we investigate whether plant survival rates differ between multinationals and indigenous plants. Second, we analyse whether employment is more unstable in multinationals. As regards the first aspect we find that multinationals are more likely to exit the market than indigenous plants when controlling for other plant and industry specific characteristics. In terms of employment persistence we find that new jobs generated in MNCs appear to be more persistent than jobs generated in indigenous plants. In contrast, they are not any more or less likely to reverse employment reductions, all other things being equal.
Keywords: 330; Multinationales Unternehmen; Personalbedarf; Volatilität; Verarbeitendes Gewerbe; Irland